Comparison Between Measured and Empirically Predicted Radio Wave Pathloss in Rural Environment - Sevan Siyyah Abdullah; Sattar Othman Hasan (Zanco Journal of Pure and Applied Sciences, 2021)
In this study a comparative analysis of various empirical models for estimating radio wave propagation path losses with those measured experimentally for the rural area in Erbil city is presented. In Gazna village near the center of the Erbil city, one of the Korek telecommunication towers is selected for the purpose of comparative analysis and seven different empirical models were utilized. The implemented models are free space model, Electronic Communication Committee (ECC-33), Stanford Interim University (SUI), Optimization Cost-231, Okumura-Hata, Egli, and Ericson models. The data were collected at operating frequencies of 1800 MHz and 2100 MHz using drive test equipment with Sony-Ericson mobile phone to measure received signal strength. Generally, the analyzed results, which are based on the Mean Absolute Percentage Error (MAPE) values, shows that the Egli and ECC-33 overestimated while both FSPL and Okamura-Hata are underestimated path loss values. In addition, the SUI and Optimized-Cost-231 models are providing minimum MAPE path loss values which are 0.49 and 0.55 at 1800 MHz and 0.07 and 0.16 at 2100 MHz, respectively. Therefore, in order to improve network performance and accurate estimation of financial feasibility, these two models especially SUI model can be used successfully and confidently in the design of the wireless communication system in the rural area of Erbil city in Kurdistan region of Iraq.